2022
DOI: 10.1088/1755-1315/1041/1/012067
|View full text |Cite
|
Sign up to set email alerts
|

The Composition of Goat Milk Kefir Added with Moringa oleifera Leaf Powder

Abstract: Goat milk kefir has gained popularity as a functional food. Incorporating natural ingredients with functional properties into kefir making could increase the functional properties in the kefir product. Moringa oleifera leaf has been extensively used for traditional medicine due to its multifunctional properties. This study aimed to investigate the chemical properties of goat milk kefir added with moringa leaf powder. The study was conducted in a Completely Randomized Design, using five treatments and five repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
2
2
Order By: Relevance
“…GMK+LC+OM sample showed the lowest protein content of other samples, which demonstrated a significant effect (P<0.05). The average protein level in this study was 4.11-4.92%, which was not far different from the previous study on kefir enriched with Moringa leaves (4.68-5.3%) (Endah et al, 2022), and kefir combined with colostrum (3.8-7.32%) (Setyawardani et al, 2020). Kefir product in this study had lower water content than that of cow milk kefir (89.08%) and soymilk kefir (91.77%), higher protein content (3.94-4.92%) than cow milk kefir (3.75%) and soymilk kefir 1.87%), and almost equal ash to that of cow milk kefir (0.64%) but higher than that of soymilk kefir (0.37%) (Yirmibeşoğlu & Öztürk, 2020).…”
Section: Physicochemical Analysiscontrasting
confidence: 91%
See 2 more Smart Citations
“…GMK+LC+OM sample showed the lowest protein content of other samples, which demonstrated a significant effect (P<0.05). The average protein level in this study was 4.11-4.92%, which was not far different from the previous study on kefir enriched with Moringa leaves (4.68-5.3%) (Endah et al, 2022), and kefir combined with colostrum (3.8-7.32%) (Setyawardani et al, 2020). Kefir product in this study had lower water content than that of cow milk kefir (89.08%) and soymilk kefir (91.77%), higher protein content (3.94-4.92%) than cow milk kefir (3.75%) and soymilk kefir 1.87%), and almost equal ash to that of cow milk kefir (0.64%) but higher than that of soymilk kefir (0.37%) (Yirmibeşoğlu & Öztürk, 2020).…”
Section: Physicochemical Analysiscontrasting
confidence: 91%
“…FFA is one of the vital parameters that affect the flavor and aroma of fermented milk. The estimated FFA values in this study were 3.78-4.98%, which was higher than 0.24-0.49% of goat milk kefir added with Moringa oleifera leaf powder (Endah et al, 2022), but lower than 5.11-8.59% (Setyawardani et al, 2017). FFA is derived from degradable milk due to the activities of microflora from the kefir grains.…”
Section: Physicochemical Analysiscontrasting
confidence: 59%
See 1 more Smart Citation
“…In addition, Suhartanti (2014) found that kefir manufactured from goat milk has antibacterial activity towards Staphylococcus aureus with an inhibition zone of 5.67 mm. Many research has been done on kefir based on the origin of kefir grain, such as Thailand kefir (Luang-In and Deeseenthum, 2016); and milk type, such as goat-milk kefir (Martharini and Indratiningsih, 2017;Endah et al, 2022). Therefore, innovation is required in establishing kefir as a functional food by integrating commonly accessible and inexpensive components.…”
Section: Introductionmentioning
confidence: 99%